1983
DOI: 10.1093/carcin/4.7.917
|View full text |Cite
|
Sign up to set email alerts
|

Induction and repair of DNA damage in normal and ataxiatelangiectasia skin fibroblasts treated with neocarzinostatin

Abstract: Cells from patients with the hereditary multisystem disorder ataxia-telangiectasia (A-T) are hypersensitive to the cytotoxic action of DNA-breaking agents, such as X-rays, bleomycin and neocarzinostatin (NCS). A defect in the repair of a certain DNA lesion induced by all three agents may underlie this hypersensitivity. This DNA lesion may be a certain type of DNA strand break. Most of the previous experiments done with X-rays and bleomycin failed to show any retardation in the rejoining of DNA strand breaks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…In addition, anti-Rad51 antibodies were used as a probe of the homologous recombination route for DSB repair. As opposed to nontreated cells, WCEs from Ncs-treated cells contain ␥-H2AX as expected given the high DNA DSB inducing potency of Ncs (32). In addition, XRCC4 in the WCEs of Ncs-treated cells was detected essentially as a slow migrating form.…”
Section: Isolation Of Protein Fractions Resistant To Detergent Extracmentioning
confidence: 52%
See 2 more Smart Citations
“…In addition, anti-Rad51 antibodies were used as a probe of the homologous recombination route for DSB repair. As opposed to nontreated cells, WCEs from Ncs-treated cells contain ␥-H2AX as expected given the high DNA DSB inducing potency of Ncs (32). In addition, XRCC4 in the WCEs of Ncs-treated cells was detected essentially as a slow migrating form.…”
Section: Isolation Of Protein Fractions Resistant To Detergent Extracmentioning
confidence: 52%
“…The time course of appearance of this recruitment paralleled that of the DSB-specific induction of H2AX phosphorylation. In addition and for the milder doses of Ncs, the disruption of NHEJ protein recruitment and dephosphorylation of ␥-H2AX occurred concomitantly with a kinetics compatible with the rejoining kinetics of Ncs-induced DSBs generated in normal cells (32). The mobilized NHEJ proteins associate in complexes as demonstrated by their co-immunoprecipitation from the P2 fraction of drug-treated cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Despite differences in chemistry and/or localization of DNA damage between IR and radiomimetic drugs, to the best of our knowledge C-1027 is the only agent able to stimulate p53 Ser-15 phosphorylation and DNA replication inhibition in an ATMϪ cell line. Reports have been published showing that several other radiomimetic compounds (for example, bleomycin and neocarzinostatin) induced radioresistant DNA synthesis and increased cell death in ATM-deficient cells (41,42). Compared with the related enediyne neocarzinostatin, C-1027 independence on ATM activity for stimulating p53 phosphorylation is somewhat unexpected since we have shown recently that both C-1027 and neocarzinostatin induced similar changes in Replication Protein A (RPA) protein status in the 293 human embryonic kidney cell line (43).…”
Section: Discussionmentioning
confidence: 99%
“…Van der Schans et al (1983) showed that the fraction of rapidly repaired dsb induced by neutrons was not significantly different from that after t-irradiation. Consequently, the explanation that the rapidly rejoined dsb could have been induced artificially at ssb sites during the elution procedure, is untenable.…”
Section: Modification Of the Ratio Of Dsb And Ssbmentioning
confidence: 91%